A Ruthenium Complex–Porphyrin–Fullerene‐Linked Molecular Pentad as an Integrative Photosynthetic Model. (14th February 2017) - Yamamoto, Masanori; Föhlinger, Jens; Petersson, Jonas; Hammarström, Leif; Imahori, Hiroshi
Abstract: A ruthenium complex, porphyrin sensitizer, fullerene acceptor molecular pentad has been synthesized and a long‐lived hole–electron pair was achieved in aqueous solution by photoinduced multistep electron transfer: Upon irradiation by visible light, the excited‐state of a zinc porphyrin ( 1 ZnP*) was quenched by fullerene (C60 ) to afford a radical ion pair, 1, 3 (ZnP .+ ‐C60 .− ). This was followed by the subsequent electron transfer from a water oxidation catalyst unit (Ru II ) to ZnP .+ to give the long‐lived charge‐separated state, Ru III ‐ZnP‐C60 .−, with a lifetime of 14 μs. The ZnP worked as a visible‐light‐harvesting antenna, while the C60 acted as an excellent electron acceptor. As a consequence, visible‐light‐driven water oxidation by this integrated photosynthetic model compound was achieved in the presence of sacrificial oxidant and redox mediator.